Self-adhesive resin cements: pH-neutralization, hydrophilicity, and hygroscopic expansion stress - Rödel, Lena; Bednarzig, Vera; Belli, Renan; Petschelt, Anselm; Lohbauer, Ulrich; Zorzin, José Ignacio (Clinical Oral Investigations, 2016)
The objective of the study was to investigate the relationship between pH-neutralization, hydrophilicity, and free hygroscopic expansion stress of self-adhesive resin cements (SARCs) after storage in artificial saliva.The SARCs RelyX Unicem Automix 2 (RX2, 3 M ESPE), iCEM (iCEM, Heraeus) and Maxcem Elite (MCE, Kerr) were under investigation in this study. Cylinders (height × diameter, 6 × 4mm) were prepared from each material and stored in artificial saliva (7d at 37 °C). Cylinder height was measured at baseline and after 7 days. After storage, the compression modulus was measured to calculate the free hygroscopic expansion stress. For pH-neutralization and hydrophilicity assessment, disks (height × diameter, 1 × 1.5 mm) were prepared, covered with electrolyte, and monitored over 24 h at 37 °C. Hydrophilicity was assessed using the static sessile drop technique at baseline and at different time intervals up to 24 h. Data were analyzed using one-way ANOVA and post hoc Student-Newman-Keuls test (S-N-K, ? = 0.05).After 24 h, RX2 (pH24h 4.68) had a significantly higher (p < 0.05) pH-value than MCE (pH24h 4.2) and iCEM (pH24h 3.23). iCEM showed the significantly highest hydrophilicity (p < 0.05) after 24 h (?24h 85.02°), while MCE resulted lower (?24h 113.01°) in comparison with RX2 (?24h 108.11°). The resulting hygroscopic expansion stress of iCEM (29.15 MPa) was significantly higher (p < 0.05) compared to RX2 (14.5 MPa) and MCE (21.02 MPa).The material with lowest pH-neutralization capacity displayed higher hydrophilicity after 24 h and higher hygroscopic expansion stress after 7 days compared to those with high pH-neutralization.Remnant hydrophilicity due to low pH-neutralization of SARCs could lead to cement interface stress build-up and long-term failure of silicate ceramic restorations.
EVALuna2:24695